In silico strategy for isoform-selective 5-HT2AR and 5-HT2CR inhibitors. Issue 2 (18th January 2021) - Geng, Xiaohui; Wang, Ying; Wang, Huibin; Hu, Baichun; Huang, Junhao; Wu, Yiheng; Wang, Jian; Zhang, Fengjiao
Abstract : 5-HT2A R and 5-HT2C R are widely expressed throughout the brain and have been drawing significant clinical interest due to their involvement in mediating mental disorders. Abstract : 5-HT2A R and 5-HT2C R are widely expressed throughout the brain and have been drawing significant clinical interest due to their involvement in mediating mental disorders. Indeed, 5-HT2A R acts as a biological target for atypical antipsychotics and addiction, and 5-HT2C R also serves as a therapeutic target for depression and addiction. Given that 5-HT2A R and 5-HT2C R provide opposing influences upon DA mesocorticoaccumbens output, plus 5-HT2C R is thought to be involved in appetite that might result in the side effect of weight gain, it makes great sense for drug design to provide the selective mechanisms of 5-HT2A R and 5-HT2C R in order to meet the increasing need for more effective medications. Toward this end, the structure and chemical properties of crucial residues between 5-HT2A R and 5-HT2C R were analyzed based on their individual crystal structures. Moreover, pruvanserin and RS102221, the highly selective antagonists of 5-HT2A R and 5-HT2C R, respectively, were employed to illuminate the selective binding modes through a comprehensive application of in silico methods, including molecular docking, molecular dynamic simulations, MM-GBSA, alanine scanning mutagenesis, DFT technologies, and structure-based pharmacophore modeling. It was found that although 5-HT2A/C R isoforms share high sequence homology in active pockets, they do possess distinctive physiological functions. The key residues that contributed to the selectivity between 5-HT2A/C R are ASP155, LEU229, TRP336, and PHE340 of 5-HT2A R, as well as ASP134, LEU209, and PHE328 of 5-HT2C R. Moreover, in view of the much smaller hydrophobic region of the 5-HT2A R, a ligand with reduced side chain volume would increase its selectivity to 5-HT2A R, and vice versa . In addition, considering that RS102221/5-HT2C R formed more water bridges compared to that of pruvanserin/5-HT2A R, hydrogen bonding interactions should be emphasized in the design of 5-HT2C R selective inhibitors. Collectively, this study provided novel insights into the rational selectivity mechanisms of 5-HT2A R/5-HT2C R inhibitors, which laid important foundations for designing selective inhibitors towards 5-HT2A R and 5-HT2C R.